Mobile entertainment adoption among UiTM Shah Alam students - Zainol, Rosmayanti (2006)
Mobile entertainment is defined as any leisure activities which performed through mobile devices whether this activities utilizes the mobile network or not and incurs a cost or does not incurs a cost. Mobile entertainment also can be defined as a subset of mobile commerce application. Advancement in mobile industry provides a lot of mobile commerce application. At the end of year 2005, the penetration rate for ownership of mobile phone almost 70 percent. This rate increase ahnost 20 percent compare to the last year penetration rate. Some popular mobile applications are mobile banking and mobile entertainment. User can use all those application anytime and anywhere. This study seeks to identify the factors that influence mobile entertainment adoption and to identify the relationship among the factors that influence the adoption of mobile entertainment. This study use Theory of Reasoned Action (TRA) to determine factors influencing the use of mobile entertainment applications. Primary data were collected through questionnaires. 300 students were randomly selected in order to participating in this survey. From 300 sets of questionnaires only 284 set questionnaires were obtain back. Correlation coefficient analyses result shows there is significant relationship between factors that influences the mobile entertainment use. There are seven from nine hypotheses have significant and positive relationships among each of variables. There are some limitations in this research and some recommendations are identified in order to overcome the limitations. This study can be extended to different type of respondents.